The association of ITGB3 gene and NOS3 gene with the severity of coronary artery disease with and without type 2 diabetes - Elvira F. Muslimova (Endocrinology Research Centre, 2016)
Type 2 diabetes (T2DM) is one of the key predictors of coronary artery disease (CAD) and its complications. Currently, along with metabolic risk factors for CAD, much attention has been given to the study candidate genes, including platelet fibrinogen receptor gene ITGB3 and the gene NOS3 of endothelial NO-synthase type 3.Aim. To estimate the associations of T1565C ITGB3 and T-786C NOS3 polymorphisms with the clinical condition of russian patients from West Siberian region with concomitant development of coronary artery disease and type 2 diabetes.Materials and methods. The study included 237 CAD patients; 78 (32.9%) of them had T2DM. The genotyping was performed by allele-specific polymerase chain reaction. Comparison of quantitative variables between groups with different genotypes was done by Mann-Whitney U test or Kruskal-Wallis test. Comparison of discrete parameters was done by Pearson χ2 test or Fisher's exact test.Results. Genotype 786CC (NOS3) (p=0,039) and allele 1565C (ITGB3) (p=0,045) were less common in the group CAD+T2DM than in the group CAD without T2DM. But in the group CAD+T2DM the frequency of obesity was higher among carriers of 1565C allele than in homozygotes 1565TT (p=0,039), and carriers of 786C allele have the highest concentration of glucose compared to homozygous 786TT (p=0,018). Furthermore, 786C allele is associated with obesity in the group of patients without T2DM detected (p = 0,015).Conclusion. Carriage of 1565C (ITGB3) allele and 786C (NOS3) allele can be considered as predictors of adverse course of the disease at concomitant development of CAD and T2DM.